2016
DOI: 10.4236/acs.2016.61002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Aerosol Optical Properties and Identification of Different Aerosol Types Based on AERONET Data over Sub-Sahara West-Africa

Abstract: The uncertainty in the quantification of aerosol properties such as concentration, size, and composition, spatially and temporally makes regional studies important. Therefore, this study presents seasonal variations of aerosol optical properties over Ilorin (8˚32'N, 4˚34'E), Nigeria. Long-term (1998-2013) records of aerosol optical depth (AOD) and angstrom exponent α, from ground-based Aerosol Robotic Network (AERONET) are used to study the seasonal variability, characteristics and types of aerosol. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The contribution of advected mineral dust and biomass burning aerosol by northerly winds is also high during the dry season (Balarabe et al, 2016). Following Kaufman et al (2000), large particles (dust or maritime aerosols) are dominant in the size distribution when the Ångström coefficient is below 0.7, although Toledano et al (2007) have reported a threshold of 1.05.…”
Section: Aodmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of advected mineral dust and biomass burning aerosol by northerly winds is also high during the dry season (Balarabe et al, 2016). Following Kaufman et al (2000), large particles (dust or maritime aerosols) are dominant in the size distribution when the Ångström coefficient is below 0.7, although Toledano et al (2007) have reported a threshold of 1.05.…”
Section: Aodmentioning
confidence: 99%
“…Following Kaufman et al (2000), large particles (dust or maritime aerosols) are dominant in the size distribution when the Ångström coefficient is below 0.7, although Toledano et al (2007) have reported a threshold of 1.05. A low value, typically below 0.8, of the Ångström exponent associated with high AOD, typically above 0.6 (Verma et al, 2015), indicates a significant contribution of coarse dust-like particles to the AOD (Balarabe et al, 2016).…”
Section: Aodmentioning
confidence: 99%
“…The AOT values are lower for fine aerosols and higher for coarse aerosols. In the literature, different criteria have been proposed to identify dust aerosols at different locations: for example, α < 0.6 (Dubovik et al, 2002;Brindley et al, 2015), α < 0.8 (Eck et al, 2005;Che et al, 2013), α < 1 (Eck et al, 1999;Schuster et al, 2006;Papaynannis et al, 2007;Yoon et al, 2012;Valenzuela et al, 2014;Zu et al, 2014;Pakszys et al, 2015) and α < 1.4 (Gobbi et al, 2007;Pereira et al, 2011;Shinozuka et al, 2011); similarly, AOT > 0.11 (Toledano et al, 2007;Balarabe et al, 2016), AOT > 0.2 (Salinas et al, 2009;Pakszys et al, 2015) and AOT > 0.25 (Guleria et al, 2012) have been recommended to identify dust aerosols. After considering all these studies, we have adopted the ranges of AOT and AE for off Somalia as follows: AE less than 1, and AOT at 440 nm (τ 440 ) greater than 0.2 (i.e., α < 1 and τ 440 > 0.2) are designated as DOT or dust aerosols.…”
Section: Derivation Of Dust Optical Thickness (Dot)mentioning
confidence: 99%
“…To better depict aerosol properties, many studies were carried out in the last decades [10][11][12][13][14][15][16][17]. Some of the studies [10][11][12][13] classify aerosol types by thresholds of aerosol properties, such as aerosol optical depth (AOD),Ångström exponent (AE), fine-mode fraction (FMF), single scattering albedo (SSA), or their combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies [10][11][12][13] classify aerosol types by thresholds of aerosol properties, such as aerosol optical depth (AOD),Ångström exponent (AE), fine-mode fraction (FMF), single scattering albedo (SSA), or their combinations. For example, to discriminate aerosol types of biomass-urban, desert dust, clean maritime, and mixed-type, appropriate thresholds for AOD and AE are applied [10].…”
Section: Introductionmentioning
confidence: 99%